Clinical Conditions, Mortality, and Associated Risk Factors in Patients with Flail Chest Injuries: A Tertiary Care Experience - Md Mobarak Hossain; Faquir Walid Shah; Md Murad Hossain; Ashraful Alam Khan; Tazrin Farhana; Md Rashedul Hasan; Md Anwar Hossain; Mohammad Saiful Hoq Ibna Majib; Rokshana Akhter; Md Nazmul Islam (Chest & Heart Journal, 2026)
Background: Flail chest is a severe thoracic injury associated with significant morbidity and mortality. Understanding the clinical profile, outcomes, and risk factors is crucial for effective management. This study aimed to evaluate the clinical conditions, outcomes, and predictors of mortality in patients with flail chest injuries at a tertiary care center. Method: This cross-sectional study was conducted in the Department of Thoracic Surgery, National Institute of Diseases of Chest & Hospital (NIDCH), Dhaka, Bangladesh, from January 2010 to December 2010. This study included 60 patients with flail chest injuries who were admitted at this study institution. Results: The mean age of patients was 39.85 ± 16.3 years, with a majority over 40 years (45%). Males predominated (72%), with a male-to-female ratio of 2.5:1. Central flail chest was the most common type (63.3%), and road traffic accidents were the leading cause of injury (80%). All patients presented with chest pain, while 63.3% had respiratory distress and 25% exhibited cyanosis. The mean number of fractured ribs was 7 ± 1.5. Pneumonia developed in 31.7% of patients, and adult respiratory distress syndrome occurred in 8.3%. The mean hospital stay was 12.2 ± 1.25 days, and the overall mortality rate was 10%. Significant predictors of mortality included age e”60 years (83.3% of non-survivors vs. 7.4% of survivors, p < 0.0001), pneumonia (66.7% vs. 11.1%, p = 0.0006), and requirement for mechanical ventilation (83.3% vs. 5.6%, p < 0.0001). Conclusion: Flail chest is associated with substantial morbidity and mortality. Older age, pneumonia, and mechanical ventilation are significant predictors of mortality, highlighting the need for early recognition and intensive management of high-risk patients. Chest Heart J. 2025; 49(1) : 22-28